Aspek Hukum Pertimbangan Mahkamah Agung Mengabulkan Permohonan Kasasi Penuntut Umum Terhadap Putusan Bebas dalam Perkara Tindak Pidana Usaha Pertambangan Tanpa Izin - Ardiansyah Putra (Verstek, 2019)
This research aims to know the legal aspects of the consideration of the Supreme Court granted the petition for Cassation of the prosecutor in case of Ilegal Mining. The research method used was the normative legal research. The approach used was approach legislation and the approach to the case. The source of the legal materials used are primary and secondary legal materials. Note that the reason the prosecutor fled a cassation over the verdict of the District Court’s of Solok verdict number: 57/Pid.sus/2013/PN.Slk has been according to Article 256 KUHAP jo. Article 158 Act No. 4 of the year 2009, then the Supreme Court authorized the application for appeal against the verdict.Keywords: Cassation, Illegal Mining,Verdict